Nutritional Additives of Distillery Spentwash on the Production of Leafy Medicinal Plants in Normal and Spentwash Treated Soil - C. S. Chidankumar2, S. Chandraju1* and (Journal of Phytology, 2010)
Cultivation of some leafy medicinal plants namely, Coriander (Coriandrum sativum), Dill (Anethum graveolens), Pudina /Spearmint (Mentha viridis), Fenugreek/Methi (Trigonella foenum-graecum) was made by irrigation with distillery spentwash of different proportions. The spentwash i.e., primary treated spentwash (PTSW) and 33% spentwash were analyzed for their plant nutrients such as nitrogen, phosphorous, potassium and other physical and chemical parameters. Experimental soils i.e, normal soil (plot-1) and spentwash treated (plot-2) soils were tested for their chemical and physical parameters. The sets/seeds (Namadhari and Mayhco) of medicinal plants were sowed in the prepared land and irrigated with raw water (RW) and 33% spent wash. Influence of spentwash in normal and spentwash treated soils on the nutrients plants were investigated at their respective maturity. It was found that the nutrients of all medicinal plants were high in 33% than raw water irrigation. Further, the nutritive values were moderately high in spentwash treated soil (plot-2) than normal soil (plot-1) and raw water irrigations for all plants.